Clinical Outcomes of COVID-19 and Impact on Disease Course in Patients with Inflammatory Bowel Disease. (30th November 2021) - Wetwittayakhlang, Panu; Albader, Farah; Golovics, Petra A; Hahn, Gustavo Drügg; Bessissow, Talat; Bitton, Alain; Afif, Waqqas; Wild, Gary; Lakatos, Peter L
Abstract : Background and Aims . The impact of COVID-19 has been of great concern in patients with inflammatory bowel disease (IBD) worldwide, including an increased risk of severe outcomes and/or possible flare of IBD. This study aims to evaluate prevalence, outcomes, the impact of COVID-19 in patients with IBD, and risk factors associated with severe COVID-19 or flare of IBD activity. Methods . A consecutive cohort of IBD patients who were diagnosed with COVID-19 infection and followed up at the McGill University Health Care Centre was obtained between March 1, 2020, and April 30, 2021. Demographics, comorbidities, IBD (type, treatments, pre- and post-COVID-19 clinical activity, biomarkers, and endoscopic activity), and COVID-19-related outcomes (pneumonia, hospitalization, death, and flare of IBD disease) were analyzed. Results . A cohort of 3, 516 IBD patients was included. 82 patients (2.3%) were diagnosed with COVID-19 infection (median age: 39.0 (IQR 27.8–48.0), 77% with Crohn's disease, 50% were female). The prevalence of COVID-19 infection in IBD patients was significantly lower compared to the general population in Canada and Quebec (3.5% versus 4.3%, p < 0.001 ). Severe COVID-19 occurred in 6 patients (7.3%); 2 patients (2.4%) died. A flare of IBD post-COVID-19 infection was reported in 8 patients (9.8%) within 3 months. Biologic therapy was held during active COVID-19 infection in 37% of patients. Age ≥55 years (odds ratio (OR): 11.1, 95% CI: 1.8–68.0), systemic corticosteroid use (OR: 4.6, 95% CI: 0.7–30.1), active IBD (OR: 3.8, 95% CI: 0.7–20.8), and comorbidity (OR: 4.9, 95% CI: 0.8–28.6) were factors associated with severe COVID-19. After initial infection, 61% of IBD patients received COVID-19 vaccinations. Conclusion . The prevalence of COVID-19 infection among patients with IBD was lower than that in the general population in Canada. Severe COVID-19, mortality, and flare of IBD were relatively rare, while a large proportion of patients received COVID-19 vaccination. Older age, comorbidities, active IBD disease, and systemic corticosteroid, but not immunosuppressive or biological therapy, were associated with severe COVID-19 infection.